The Effect of Online Discovery-Inquiry Learning on Improving Critical Thinking Ability and Concept Mastery in Temperature and Heat Materials - Fildzah Purvita Dewi; Lia Yuliati; Edi Supriana (Jurnal Pendidikan Sains, 2023)
The research endeavors to investigate the impact of implementing discovery-inquiry learning concerning the topic of temperature and heat on the enhancement of students’ critical thinking abilities and concept mastery. The study adopted a quasi-experimental design, employing a pretest-posttest control group framework. A cluster random sampling technique was applied to select the research sample, which comprised 36 students from class XI MIPA 3 (control group) and class XI MIPA 4 (experimental group) at SMA Negeri Rambipuji. The assessment instruments employed were two essay-shaped tests, specifically designed for evaluating critical thinking ability and concept mastery. Data analysis involved the utilization of independent sample t-test and effect size test. The results revealed a statistically significant improvement in students’ critical thinking ability and concept mastery with a robust effect size, categorizing the impact of discovery-inquiry learning as substantial. Consequently, it can be inferred that discovery-inquiry learning is efficacious in augmenting students’ critical thinking abilities and concept mastery pertaining to the subject of temperature and heat.DOI: 10.17977/jps.v11i22023p065